The Impact of Social Media on Muslim Religious Identity in the 21st Century Social and Cultural Perspective - Enjang; Didi Supandi (al-Afkar, Journal For Islamic Studies, 2025)
Social media has become a global phenomenon that influences various aspects of life, including the religious identity of muslims in the 21st century. The purpose of this study is to explore the impact of social media on the religious identity of muslims from a social and cultural perspective. With a qualitative approach based on literature analysis, this study attempts to analyze how digital platforms shape patterns of interaction, religious understanding and expression of muslim identity, the results of the study show that social media can strengthen the solidarity of the Muslim community, but also brings challenges in the form of polarization, the spread of invalid religious information and the influence of global culture thas has the potential to obscure Islamic values.